2019
DOI: 10.1530/edm-19-0002
|View full text |Cite
|
Sign up to set email alerts
|

A unique case of ectopic Cushing’s syndrome from a thymic neuroendocrine carcinoma

Abstract: Summary Ectopic adrenocorticotropic hormone (ACTH) production leading to ectopic ACTH syndrome accounts for a small proportion of all Cushing’s syndrome (CS) cases. Thymic neuroendocrine tumors are rare neoplasms that may secrete ACTH leading to rapid development of hypercortisolism causing electrolyte and metabolic abnormalities, uncontrolled hypertension and an increased risk for opportunistic infections. We present a unique case of a patient who presented with a mediastinal mass, revealed to be an ACTH-secr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Steroidogenesis inhibitors have also been studied in combination with pituitary-directed agents (pasireotide and cabergoline); however, such therapy is used in patients with persistent or recurrent CD rather than for the purpose of controlling SH [31][32][33][34]. Lawrence et al reported a patient with severe EAS, due to a thymic neuroendocrine tumor, who was successfully controlled with a combination regimen of ketoconazole and mifepristone [35]. However, it is difficult to monitor the efficacy and safety of such treatment because measuring serum cortisol and/or UFC is not objective in that case [36].…”
Section: Discussionmentioning
confidence: 99%
“…Steroidogenesis inhibitors have also been studied in combination with pituitary-directed agents (pasireotide and cabergoline); however, such therapy is used in patients with persistent or recurrent CD rather than for the purpose of controlling SH [31][32][33][34]. Lawrence et al reported a patient with severe EAS, due to a thymic neuroendocrine tumor, who was successfully controlled with a combination regimen of ketoconazole and mifepristone [35]. However, it is difficult to monitor the efficacy and safety of such treatment because measuring serum cortisol and/or UFC is not objective in that case [36].…”
Section: Discussionmentioning
confidence: 99%
“… 6 Thymic NETs are usually rare and account for a small percentage of malignancies, occurring more in male individuals at a ratio of 3:1. 7 Functional thymic tumors tend to have a more complicated course and rapid onset of the development of clinical symptoms when associated with endocrinopathy. Suspicion of such tumors should be raised and sought when diagnosing an ectopic Cushing's syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…There is little evidence in the literature describing Cushing's syndrome with a neuroendocrine thymic tumor 6 . Thymic NETs are usually rare and account for a small percentage of malignancies, occurring more in male individuals at a ratio of 3:1 7 . Functional thymic tumors tend to have a more complicated course and rapid onset of the development of clinical symptoms when associated with endocrinopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Thymic carcinoid can also secrete ACTH, resulting in ectopic ACTH syndrome, and causing electrolyte and metabolic abnormalities in patients. Its clinical manifestations can include typical Cushing's syndrome manifestations such as central obesity, moon-shaped face, skin ecchymosis, purple skin striae, skin pigmentation, hypertension, hyperglycemia, hypokalemia, and others (7)(8)(9)(10). It is extremely rare for patients with ectopic ACTH syndrome caused by thymic carcinoid to concurrently exhibit abnormal mental behavior, especially as the initial clinical manifestation of the tumor and can be manifested as insomnia, memory disorders and so on.…”
Section: Introductionmentioning
confidence: 99%